The currency of reciprocity - gift-exchange in the workplace - Sebastian Kube; Michel André Maréchal; Clemens Puppe (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2011)
What determines reciprocity in employment relations? We conducted a controlled field experiment to measure the extent to which monetary and non-monetary gifts affect workers' performance. We find that nonmonetary gifts have a much stronger impact than monetary gifts of equivalent value. We also observe that when workers are offered the choice, they prefer receiving the money but reciprocate as if they received a nonmonetary gift. This result is consistent with the common saying, 'it's the thought that counts.' We underline this point by showing that also monetary gifts can effectively trigger reciprocity if the employer invests more time and effort into the gift's presentation.
urn:nbn:de:swb:90-229999
Keywords: C93; J30; 330; field experiment; reciprocity; gift exchange; non-monetary gifts; in-kind gifts